Current Viewpoints on Ancient Jewish Coinage: A Bibliographic Essay - Hendin, David (2013)
This article presents a survey of recent research in pre-coinage currency of Judaea, coins of the Persian period (Philistia, Edom, Samaria, and Judaea), the Hasmonean dynasty, the Herodian dynasty, the Jewish War against Rome and the Bar Kokhba revolt. Books, articles, presentations and dissertations have added significantly to the literature; it is the author’s goal to assist the non-specialist in keeping up with the latest information and opinions.
Keywords: shekel of Tyre; shekel; prutah; Judaea; Jewish War; Jewish coins; Herodian; Hasmonean; Epigraphy; Bar Kokhba